Vascular and Metabolic Risk Factors, Carotid Atherosclerosis and Vascular Cognitive Impairment in a First Nations Population - Fergenbaum, Jennifer
The objectives of the thesis were to examine the associations between vascular and metabolic risk factors, carotid atherosclerosis and cognitive function in a Canadian First Nations population. Eligible individuals were ≥18 years and with First Nations status who had undergone cognitive function assessment by the Clock Drawing Test (CDT) and the Trail Making Test Parts A and B. Parts A and B were combined into an executive function score (TMT-exec). Anthropometric, vascular and metabolic risk factors were assessed by interview, clinical examinations and blood tests. Doppler ultrasonography assessed carotid atherosclerosis (carotid stenosis, plaque volume). For the 190 individuals with TMT-exec scores, obese individuals were at a 4-fold increased risk for lowered cognitive performance compared to those who were not obese (odds ratio [OR]: 3.77, 95% confidence interval [CI]: 1.46-9.72). Those having an increased waist circumference also had 5 times the risk compared to those without an increased waist circumference (OR: 5.41, 95% CI: 1.83-15.99). Individuals having the metabolic syndrome were at a 4-fold increased risk compared to those without the metabolic syndrome (OR: 3.67, 95% CI: 1.34-10.07). No other cardiovascular risk factors were associated and no associations were shown for the CDT. For TMT-exec only, individuals with elevated levels of left (LCS) and total carotid stenosis (TCS) were less likely to demonstrate lowered cognitive performance (LCS, OR: 0.47, 95% CI: 0.24-0.96; TCS, OR: 0.40, 95% CI: 0.20-0.80). In structural equation modeling, for every 1-unit change in the anthropometric factor in kg/m2, there was a 0.86-fold decrease in the percent of TCS (p<0.05). The etiology of VCI is vascular and is affected by non-traditional risk factors such as obesity. The health effects of obesity beyond traditional disease endpoints warrants further study. Mild-moderate levels of carotid stenosis are not detrimental to cognitive functioning and may additionally include acting as a mediator. PhD